Preservation of Protected Forest Functions: The Effectiveness of Customary Sanctions (Givu) in To Kulawi - Insarullah, Insarullah; Imran, Imran; Ikbal, Ikbal; Arfanita, Arfanita (Jurnal Ilmu Hukum Kyadiren, 2025)
This study aims to examine the role of the To Kulawi traditional institution and assess the implementation of customary sanctions (Givu) in preserving the function of protected forests in Sigi Regency. It is expected to contribute to strengthening the To Kulawi traditional institution. The research employs an empirical legal approach, focusing on the practical application of law (law in action) within society. The findings indicate that the existence and role of the To Kulawi traditional institution are essential for preserving the function of protected forests and implementing customary sanctions (Givu) in Sigi Regency. The application of these customary sanctions within the To Kulawi indigenous community has been effective and is widely accepted as a governing norm for forest preservation in the region. Therefore, it is recommended to enhance the recognition and protection of the To Kulawi traditional institution through policies enacted by regional and village governments, such as regional or village regulations.